2013
DOI: 10.1016/j.psychres.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Right fronto-parietal dysfunction underlying spatial attention in bipolar disorder

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Psychiatry Research. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Psychiatry Research, 210, 2, 15 December 2013, 10.1016/j.psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Hausmann et al, 2002;2003a;2003b;Najt et al, 2013). The task was comprised of 17 horizontal, black lines of 1 mm width on a white sheet of A4 paper.…”
Section: Line Bisection (Lb) Taskmentioning
confidence: 99%
“…Hausmann et al, 2002;2003a;2003b;Najt et al, 2013). The task was comprised of 17 horizontal, black lines of 1 mm width on a white sheet of A4 paper.…”
Section: Line Bisection (Lb) Taskmentioning
confidence: 99%
“…Furthermore, RSNs show consistency across different subject groups, analysis methods, and types of scanning protocols . Moreover, several RSNs have been implicated in mood disorders: the default mode network (DMN); the left and right lateralized frontoparietal networks (FPN); and the salience network (SN) …”
mentioning
confidence: 99%
“…This finding suggests an altered involvement of neural circuits related to cognitive control processes related to this network, specifically monitoring and conflict-resolution processes (Dosenbach et al, 2008), which has been suggested previously (Sylvester et al, 2012) and may be one of the causes for reading comprehension deficit in individuals with mood disorders. Another possibility is dysfunction in functional connectivity of the fronto-parietal network in youth with mood disorders (Sylvester et al, 2012), and more specifically, the right fronto-parietal network (Tamnes et al, 2013, Najt et al, 2013), which also is involved in working memory and phonological processing (Tamnes et al, 2013). Because both the cingulo-opercular and fronto-parietal networks can be easily identified during rest (Dosenbach et al, 2008), a future study involving a resting-state functional connectivity analysis, complementing to the current structural connectivity study and focusing specifically on these networks and their association with reading scores, is needed to confirm this point.…”
Section: Discussionmentioning
confidence: 99%